Genomic Description of ‘Candidatus Abyssubacteria,’ a Novel Subsurface Lineage Within the Candidate Phylum Hydrogenedentes - Momper, Lily; Aronson, Heidi S.; Amend, Jan P. (Frontiers in Microbiology, 2018)
The subsurface biosphere is a massive repository of fixed carbon, harboring approximately 90% of Earth’s microbial biomass. These microbial communities drive transformations central to Earth's biogeochemical cycles. However, there is still much we do not understand about how complex subterranean microbial communities survive and how they interact with these cycles. Recent metagenomic investigation of deeply-circulating terrestrial subsurface fluids revealed the presence of several novel lineages of bacteria. In one particular example, phylogenomic analyses do not converge on any one previously identified taxon; here we describe the first full genomic sequences of a new bacterial lineage within the candidate phylum Hydrogenedentes, ‘Candidatus Abyssubacteria.’ A global survey revealed that members of this proposed lineage are widely distributed in both marine and terrestrial subsurface environments, but their physiological and ecological roles have remained unexplored. Two high quality metagenome assembled genomes (SURF_5: 97%, 4%; SURF_17: 91% and 4% completeness and contamination, respectively) were reconstructed from fluids collected 1.5 kilometers below surface in the former Homestake gold mine—now the Sanford Underground Research Facility (SURF)—in Lead, South Dakota, USA. Metabolic reconstruction suggests versatile metabolic capability, including possible nitrogen reduction, sulfite oxidation, sulfate reduction and homoacetogenesis. This first glimpse into the metabolic capabilities of these cosmopolitan bacteria suggests that they are involved in key geochemical processes, including sulfur, nitrogen, and carbon cycling, and that they are adapted to survival in the dark, often anoxic, subsurface biosphere.